(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify: electronic bullying and psychological stress among middle school students, and is there a relationship between electronic bullying and psychological stress among middle school students? The research was limited to middle school students (sixth grade middle school) for the academic year 2020/2021 AD. The electronic bullying scale prepared by (Al-Dhahabi, 2017) was adopted, which consisted of (18) items. The researcher also adopted the psychological stress scale prepared by (Hamdan, 2012), which consisted of (30) items. To ensure the validity of the two scales, they were presented to a group of arbitrators and specialists, and this was achieved. Apparent honesty, as for stability, the value of the scale’s stability is reached Electronic bullying (0.90) using the Alfakrobach coefficient, while the psychological stress scale reached (0.469) and when corrected by the Spearman-Brown equation it reached (0.64) and it is an acceptable indicator of the stability of the two scales. The results appeared. The more cyberbullying among the sample members, the more psychological pressure they had. In light of the research results, the researcher recommended a set of recommendations and suggestions